Rasionalitas Siswa dalam Belajar Pasca Covid 19 Di Sekolah Dasar Perspektif Max Weber - Noblana Adib; Ismiati Ismiati (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2023)
This study explored students' rationality in post-COVID-19 learning using Weber's perspective as a framework. This qualitative study involved VI-grade students at SDN 3 Simpangkatis, Central Bangka, Bangka Belitung Islands Province as primary informants. Then, the principal and teacher of Islamic Religious Education who will provide extra instructions. The data were collected through observation, structured interviews, and documentation which were then analyzed through data reduction, data display, and data verification. Weber's rationality theory was utilized as the theoretical foundation. The findings revealed four patterns of rationality among VI-grade students at SD Negeri 3 Simpangkatis regarding post-COVID-19 in Islamic Religious Education. Firstly, there was a traditional irrational pattern, where some students preferred playing games over studying. Secondly, an irrational affective pattern was observed, where students showed enthusiasm to be class champions, but they lacked of proper planning. Thirdly, instrumental rationality was shown by students who took private lessons and purchased Islamic Religious Education books to enhance their knowledge and achieve optimal learning outcomes. Lastly, a value-based rationality pattern was identified, where students prioritized comprehensive understanding of the subject matter rather than solely focusing on learning outcomes or being the class champions. To accomplish this, these students attended private lessons, reviewed the learning material at home, performed reading and re-reading, and memorized the verses and hadiths.